2015
DOI: 10.1007/s11832-015-0665-9
|View full text |Cite
|
Sign up to set email alerts
|

Dega osteotomy for the management of developmental dysplasia of the hip in children aged 2–8 years: Results of 58 consecutive osteotomies after 13–25 years of follow-up

Abstract: PurposeDevelopmental dysplasia of the hip (DDH) is a term used to cover a broad spectrum of anomalies ranging from mild dysplasia to high-riding dislocations. We report the management of DDH in children using the Dega osteotomy and their long-term follow-up.MethodsFifty-eight hips from 48 children younger than 8 years treated using the Dega osteotomy between January 1988 and October 2000 were included in this multcenter study. Both prospective (41 hips) and retrospective (17 hips) cases were included, and foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 21 publications
(35 reference statements)
3
30
0
2
Order By: Relevance
“…It is claimed that as long as the triradiate cartilage is still open and growing, there is a possibility of achieving a stable concentric reduction. 1 In this study, the final radiological evaluation was 78.8% of favourable results (excellent and good) and 21.2% of unfavourable results. There was no statistically significant correlation between the outcome and the age of the patients at the time of surgery.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…It is claimed that as long as the triradiate cartilage is still open and growing, there is a possibility of achieving a stable concentric reduction. 1 In this study, the final radiological evaluation was 78.8% of favourable results (excellent and good) and 21.2% of unfavourable results. There was no statistically significant correlation between the outcome and the age of the patients at the time of surgery.…”
Section: Discussionmentioning
confidence: 54%
“…This correction is in accordance with previous studies that have reported a range of AI values of 11° to 25° at the last follow-up ( Table 4 ). 1 , 16 19 This shows the high efficacy of Dega pelvic osteotomy in restoration of AI close to normal values. The upper normal limit of AI, defined as mean plus 2 sd, is 23° at age five to seven years, 20 and Severin considered that the acetabulum was normal if AI was < 21° above age ten years.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Despite the limitations presented, the radiographic data from our study showed very satisfactory results which closely resembled previous studies. 11 , 14 The restoration of joint congruence is the final goal in treating children with DDH, and through this case series we show that the modified Dega osteotomy can be used for this purpose. In the present study, there was no increase in the number of early complications.…”
Section: Discussionmentioning
confidence: 76%
“…In a similar study including 43 hips that underwent Dega osteotomy and followed-up for 2 years in average, unsatisfactory results were obtained in the radiographic parameters of only 5 patients (33). In another study consisting of 58 hips, the outcomes were not satisfactory in accordance with the Severin Classification in 16 hips (34). Therefore, when we examined the similar studies in the literature and considered that the outcomes were unsatisfactory only in 2 hips, it might be concluded that we obtained satisfactory results according to Severin Classification indicating the final radiographic condition of the treated hips.…”
Section: Resultsmentioning
confidence: 92%